Recent Advances in the Targeting of Epigenetic Regulators in B-Cell Non-Hodgkin Lymphoma - Ribeiro, Marcelo L. (Front Genet, 2019)
In the last 10 years, major advances have been made in the diagnosis and development of selective therapies for several blood cancers, including B-cell non-Hodgkin lymphoma (B-NHL), a heterogeneous group of malignancies arising from the mature B lymphocyte compartment. However, most of these entities remain incurable and current treatments are associated with variable efficacy, several adverse events, and frequent relapses. Thus, new diagnostic paradigms and novel therapeutic options are required to improve the prognosis of patients with B-NHL. With the recent deciphering of the mutational landscapes of B-cell disorders by high-throughput sequencing, it came out that different epigenetic deregulations might drive and/or promote B lymphomagenesis. Consistently, over the last decade, numerous epigenetic drugs (or epidrugs) have emerged in the clinical management of B-NHL patients. In this review, we will present an overview of the most relevant epidrugs tested and/or used so far for the treatment of different subtypes of B-NHL, from first-generation epigenetic therapies like histone acetyl transferases (HDACs) or DNA-methyl transferases (DNMTs) inhibitors to new agents showing selectivity for proteins that are mutated, translocated, and/or overexpressed in these diseases, including EZH2, BET, and PRMT. We will dissect the mechanisms of action of these epigenetic inhibitors, as well as the molecular processes underlying their lack of efficacy in refractory patients. This review will also provide a summary of the latest strategies being employed in preclinical and clinical settings, and will point out the most promising lines of investigation in the field.